Leveraging Quizizz for Skill-Intergrated Language Assessment in EFL Classrooms: A Literature-Based Analysis : Penelitian - Shelvi Carmelya; Masagus Firdaus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study investigates the use of Quizizz, a game-based digital platform, in assessing integrated language skills within English as a Foreign Language (EFL) contexts. Employing a qualitative library research method, the study systematically reviewed journal articles, conference proceedings, and case studies published between 2020 and 2025. The findings indicate that Quizizz has evolved from a simple quiz tool to a versatile platform capable of supporting multimodal assessments that combine reading, listening, and writing skills. The platform's interactive features, such as real-time feedback and multimedia integration, help foster learner engagement and mirror authentic language use. However, challenges remain, particularly in the assessment of speaking skills and issues of equitable access to technology. The study highlights the importance of teacher training, thoughtful instructional design, and blended assessment strategies to maximize the platform’s pedagogical potential. Overall, Quizizz offers a promising alternative for integrated language assessment, aligning with communicative language teaching principles and the demands of 21st-century EFL classrooms.